Construction raw materials in Timor Leste and sustainable development - Carvalho, Jorge (2005)
ABSTRACT: Timor Leste is the newest and one of the poorer nations in the world. One of its main challenges that could lead to poverty reduction is the reconstruction and maintenance of the infrastructures that were almost completely destroyed after its independence referendum. To achieve this, there is an imperative need for construction raw materials in a country where the extractive industry is scarce and artisanal. Available geological studies deal with the island’s geology and tectonic evolution or its oil and gas potentialities. Very few broach other geological resources. A general study of the country’s territory demonstrates that Timor Leste possesses large resources in clays, limestones and sand and gravel, which can support small- to large-scale raw material extractive industries. Some selected areas have been the target of more detailed study: Venilale and Aileu, with resources for structural ceramics and whiteware respectively, and Beheda, where a crinoid-rich limestone crops out, with potential for usage as ornamental stone. These resources are suitable for non-sophisticated small-scale mining operations that should be able to accomplish environmental and social liabilities. No public policy exists for the management of these mineral resources, which is essential for the sustainable development of Timor Leste.